Kisspeptin and RF9 prevent paroxetine-induced changes in some parameters of seminal vesicle fluid in the male rats - Bulmus, Funda Gulcu; Canpolat, Sinan; Sahin, Zafer; Bulmus, Ozgur; Serhatlioglu, Ihsan; Kelestimur, Haluk (Wiley, 2020)
The aim of the study was to examine possible impacts of paroxetine and agomelatine on the levels of some components that constitute the seminal vesicle fluid. As a second purpose, it was also aimed to examine how possible negative effects induced by paroxetine on seminal vesicle fluid components were affected by kisspeptin and RF9 (an RFamide-related peptide antagonist, RFRP). Forty-two male rats, aged 21 days, divided into six groups; control, sham, paroxetine, agomelatine, paroxetine + kisspeptin and paroxetine + RF9. Paroxetine (3.6 mg/kg) and agomelatine (10 mg/kg) were administrated by oral gavage. Kisspeptin (1 nmol) and RF9 (20 nmol) were administered intracerebroventricular (i.c.v). The experiments were ended on post-natal 120 days; fructose, vitamin E, sodium, potassium and magnesium levels were measured in seminal vesicle fluid. Fructose, vitamin E, magnesium and potassium levels were significantly decreased in seminal vesicle fluid from the rats treated with paroxetine but did not show significant differences following agomelatine administration. The co-administration of kisspeptin or RF9 with paroxetine prevented the paroxetine-induced negative effects on seminal vesicle fluid components. These results suggest that reduction in sperm fertilising ability caused by changes in seminal vesicle fluid can be seen in long-term antidepressant use. RF-9 and kisspeptin might have positive effects on long-term antidepressant use-induced infertility.
Keywords: agomelatine; kisspeptin; paroxetine; RF9; seminal vesicle fluid